Antigone's sisters : on the matrix of love - Škof, Lenart, 1972- (SUNY series in theology and continental thought., 2021)
"An original and innovative exploration of Antigone, femininity, and love in various cosmological, philosophical, and theological contexts. In Antigone's Sisters, Lenart Skof explores the power of love in our world--stronger than violence and, ultimately, stronger even than death. Focusing on Antigone, Savitri, and Mary, the book offers an investigation into various goddesses and feminine figures from a variety of philosophical, mythological, theological, and literary contexts. The book also elaborates on the feminine aspects of selected concepts from modern philosophical texts, such as the Matrix in Jakob Böhme, Clara in F. W. J. Schelling, beyng in Martin Heidegger, chóra in Jacques Derrida, and breath in Luce Irigaray's thought. Drawing on Bracha M. Ettinger's concept of matrixiality, Skof proposes a new matrixial theory of philosophy, cosmology, and theology of love. Despite its many usages and appropriations, love remains a neglected topic within Western philosophy. With its new interpretation of Antigone and related readings of Irigaray, Kristeva, and Ettinger, Antigone's Sisters aims to identify some of the reasons for this forgetting of love, and to show that it is only love that can bring peace to our ethically disrupted world."--Publisher description